2017
DOI: 10.1177/0013124517719971
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Black Male Special Education Teachers: Are Alternative Licensure Programs the Desired Route for Recruitment and Preparation?

Abstract: Many Black men interested in special education careers enroll in alternate route special education programs over traditional preparation programs. However, there is little research that focuses on their reasons for choosing special education alternate route programs and what makes these programs an effective choice for Black men pursuing teaching careers in special education. This qualitative study interviewed Black men regarding (a) reasons they chose an alternate route special education program, (b) core com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…In another study, Scott (2019) interviewed 15 BMSETs who had all used alternative routes to licensure. Participants mentioned several reasons for choosing an alternative route to licensure, including cost savings and being able to work around personal responsibilities.…”
Section: Alternative and Flexible Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Scott (2019) interviewed 15 BMSETs who had all used alternative routes to licensure. Participants mentioned several reasons for choosing an alternative route to licensure, including cost savings and being able to work around personal responsibilities.…”
Section: Alternative and Flexible Pathwaysmentioning
confidence: 99%
“…Limited studies have addressed the needs of BMSETs specifically, although some research has examined the experiences of male special education teachers (Purdy, 2009;Van Setten, 2016). Research on the specific recruitment of BMSETs and their experiences with recruitment has been limited (for exceptions see Scott, 2019;Scott & Alexander, 2019). This literature review suggests that BMSETs face distinct expectations and barriers to success, paving the way for research on the experiences of BMSETs and how they are likely to differ from teachers who are women, are White, and/or teach general education.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Instead, the call is for IHE leaders to ensure that racial diversity is a priority in hiring special education faculty members and in enrolling SETCOC into the program so that diverse representation is present and valued. Recent literature showed that faculty members and SETCOC can serve as effective recruitment sources (e.g., recruitment, hiring, and even mentoring) that affirm racially diverse candidates like Kevin that racial diversity matters and that a space exists for them in the program and in the profession (Scott, 2019;Scott & Alexander, 2019). Leaders of IHEs must be aware though that any additional responsibilities for faculty members and SETCOC in their programs to engage in recruitment can cause an overburden that can lead to burnout (Scott, 2016;Scott, 2018).…”
Section: Representation From Faculty and Setcoc In Special Educationmentioning
confidence: 99%
“…Developing creative and multiple pathways to obtain SET certification has garnered recent interest (Carver-Thomas, 2018;Scott, 2019). Examples of creative and nontraditional pathway programs include Grow Your Own programs, traditionally seen as community-driven programs designed to target community members (e.g., parents, paraprofessionals) who will be trained to become teach-ers (Gist, 2019).…”
Section: Assorted Pathway Programsmentioning
confidence: 99%
See 1 more Smart Citation